One Social Media, Distinct Habitus: Generation Z's Social Media Uses and Gratifications and the Moderation Effect of Economic Capital - Hu, Qingqing; Hu, Xue; Hou, Pan (Frontiers in Psychology, 2022)
This study aims at contributing to literature by investigating characteristics of Generation Z's social media uses and gratifications and the moderation effect of economic capital. Specifically, we employed online survey as the main research method to examine the connections between the young generation cohort's online motivations, social media practices, and economic capital. A total of 221 Chinese Generation Z social media users were recruited in the survey. Results indicated that (1) Generation Zs have different social media engagements depending on whether they were connected for daily routine alternatives or socialization; (2) the young cohorts from upper-mid-income families demonstrated a more instrumental-rational habitus to use social media more frequently as a communicative tool than those from low-income families; and (3) motivations and family income interacted to influence Generation Z's social media practices (e.g., social capital accumulating and exchanging and self-expression). Findings here provide empirical reference to deepened understandings of the interactions between social media and digital generations, and their connections with digital social inequalities.